Phonon mediated spin-filtering in a molecular junction-transistor at a non-zero temperature. (2022) - Bhattacharyya, Kuntal; Kalla, Manasa; Chatterjee, Ashok
Abstract: We study a quantum mechanical transport away from equilibrium in a molecular junction-transistor at a non-zero magnetic field and temperature. The quantum dot possesses Hubbard correlation and electron-phonon coupling, and it also interacts with the substrate phonons, which makes the transport dissipative. We use Keldysh Green's function technique under the framework of the Anderson-Holstein-Caldeira-Leggett model to calculate tunnelling current, conductance and spin polarization. It is observed that the magnetic field and temperature influence the spin-resolved transport significantly, which may be useful for tunable spin-filtration.